2022
DOI: 10.1038/s41467-022-28317-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiple expansions of globally uncommon SARS-CoV-2 lineages in Nigeria

Abstract: Disparities in SARS-CoV-2 genomic surveillance have limited our understanding of the viral population dynamics and may delay identification of globally important variants. Despite being the most populated country in Africa, Nigeria has remained critically under sampled. Here, we report sequences from 378 SARS-CoV-2 isolates collected in Oyo State, Nigeria between July 2020 and August 2021. In early 2021, most isolates belonged to the Alpha “variant of concern” (VOC) or the Eta lineage. Eta outcompeted Alpha in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 75 publications
(52 reference statements)
3
32
0
Order By: Relevance
“…An analysis has shown that the SARS-CoV-2 virus identified in Gambia is of European and Asian origin, and sequencing data matched patients' travel history ( 32 ). These analyses provided strong statistical support for a monophyletic origin of almost all of the Alpha sequences from NGA, with the most likely origin being the United States ( 33 ). Similarly, the Congolese SARS-CoV-2 sequences were divided into distinct clusters, indicating two separate introductions of the virus into the Republic of Congo ( 34 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…An analysis has shown that the SARS-CoV-2 virus identified in Gambia is of European and Asian origin, and sequencing data matched patients' travel history ( 32 ). These analyses provided strong statistical support for a monophyletic origin of almost all of the Alpha sequences from NGA, with the most likely origin being the United States ( 33 ). Similarly, the Congolese SARS-CoV-2 sequences were divided into distinct clusters, indicating two separate introductions of the virus into the Republic of Congo ( 34 ).…”
Section: Discussionmentioning
confidence: 84%
“…This is a potential cause for the severity of the second wave. The Eta variant originated in West Africa before spreading globally and represented a VOC in early 2021 ( 33 ), and this variant was distributed in 15 countries in West Africa. A previous study provided evidence of increased transmission for both Alpha and Eta variants, of which Eta appeared slightly more infectious than Alpha ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 stable overexpression in A549 cells (operationally designated as A549+ cells in this paper) was conducted, as previously described [ 40 ]. In brief, A549 cells were transfected with psPAX2, pCMV-VSVG, and pRRL.sin.cPPT.SFFV/Ace2.IRES-puro.WPRE (a gift from Caroline Goujon; Addgene plasmid #145839; RRID:Addgene145839, Addgene, Watertown, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Alpha has been successful in several countries but not in all that it reached. For example, in Brazil it could not displace Gamma (Giovanetti et al, 2022) and in Nigeria it was not as successful as Eta (Ozer et al, 2022). During the second wave, Gamma was the second lineage with the highest Ne (Fig.…”
Section: Two Different Sampling Approaches Showed the Same Patterns O...mentioning
confidence: 99%
“…Whereas Gamma dominated the Northeast region of Peru, Lambda dominated all the other regions. Delta has been able to displace Gamma in Brazil (Giovanetti et al, 2022), Beta in South Africa , and Eta in Nigeria (and West Africa) (Ozer et al, 2022). In Peru, since its arrival, the Delta variant, likely helped for the number of vaccinations, was replacing Lambda and Gamma reaching very high relative frequencies in all the Peruvian regions between the second and the third wave (October to December, 2021) (Fig.…”
Section: Two Different Sampling Approaches Showed the Same Patterns O...mentioning
confidence: 99%